2012
DOI: 10.1021/ic300609f
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Photophysical Parameters and Gold–Gold Distances in Gold(I) (4-Pyridyl)ethynyl Complexes

Abstract: The systematic analysis of the luminescence of a series of alkynyl gold derivatives with general formulas [(diphos)(AuC≡Cpy)(2)] (diphosphane =2,2'-bis(diphenylphosphanyl)propane or dppip (1), bis(diphenylphosphanyl)acetylene or dppa (2), 1,2-bis(diphenylphosphanyl)ethane or dppe (3) and 1,4-bis(diphenylphosphanyl)butane or dppb, (4), has shown a straightforward correlation between the Au(I)···Au(I) distance and the emission quantum yields and decaytimes. The analysis of the decaytimes, quantum yields and thus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
64
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 72 publications
(75 citation statements)
references
References 35 publications
7
64
1
Order By: Relevance
“…265-300 assigned to intraligand (IL) π-π* (C≡Cpy) transitions based on literature. 11,15,16,42,43 This transition exhibits some broadening (not completely vibronically resolved) which is indicative of an aggregation process where the Au-C≡Cpy moiety is directly involved. 15 Thus,  stacking together with aurophilic interactions are expected to be present in solution and should be responsible for the formation of the rod-like structures.…”
Section: Absorption and Emission Characterization In Watermentioning
confidence: 99%
See 2 more Smart Citations
“…265-300 assigned to intraligand (IL) π-π* (C≡Cpy) transitions based on literature. 11,15,16,42,43 This transition exhibits some broadening (not completely vibronically resolved) which is indicative of an aggregation process where the Au-C≡Cpy moiety is directly involved. 15 Thus,  stacking together with aurophilic interactions are expected to be present in solution and should be responsible for the formation of the rod-like structures.…”
Section: Absorption and Emission Characterization In Watermentioning
confidence: 99%
“…A lower intensity broad band or tail above 300 nm can be assigned to a σ* Au···Au -π* transition according to theoretical studies carried out recently for analogous neutral complexes. 42,44 The intraligand absorption band of 2-6 is about 20 nm red-shifted and without vibronical resolution. In the case of 2, 3, 5 and 6, this is due to the methylated pyridyl group.…”
Section: Absorption and Emission Characterization In Watermentioning
confidence: 99%
See 1 more Smart Citation
“…There are literature reports showing fluorescence lifetime of gold nanoclusters to be around a few hundred nanoseconds, which is comparable with our observation. [42][43][44][45] The mechanism of such emission is still under investigation but it is believed to be related to the charge transfer from ligand. 39,42 For example, Wu and Jin reported that the Au25SG18 -cluster has decay times of 246 nsec and 1200 nsec, where SG denotes for glutathione.…”
Section: Hydrodyanmic Diameter Of the Complexes Formed By Au And Deoxmentioning
confidence: 99%
“…As depicted in Figure 3, the SPR band is more red-shifted and broader at neutral and slightly basic media (pH 7-8), evidencing a clear enhancement of interparticle interactions. Interestingly, in the UV-Vis spectra of water solutions of free complex 1 at pH 7-8 (see Figure S7) there is a notable intensification of the broad and weak band at 300 nm, assigned to the aurophilic interactions, 29 indicating a better capacity of complex 1 to create Au(I)-Au(I) bonds at this pH. Indeed, for the NCP sample, the ratio of absorption intensities at 300 nm and 260 nm (A300/A260) is maximum at pH 7-8, confirming the higher degree of aurophilic interactions under these specific conditions ( Figure S8).…”
Section: Introductionmentioning
confidence: 99%